2019
DOI: 10.1051/matecconf/201929703003
|View full text |Cite
|
Sign up to set email alerts
|

The Step Feed Mechanisms For Auger Machines

Abstract: The paper presents the results of studies of technical solutions proposed in Kuzbass State Technical University and implemented in auger drilling equipment, characterized by the presence of a cyclic feed of a boring machine on the face and the corresponding reverse of the work by hydraulic jacks. Operation of complexes, which design feature is to provide a common plane for the axis of the boring hole and vectors of axial forces of the auger feeding mechanisms, was researched. The stress state of the cyclic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…At the same time, it is taken into account that in order to increase the stability of boring equipment when boring horizontal holes of large diameter, it is possible to use a two-stage technology, which implies boring a small-diameter pioneer hole in a direct motion with its subsequent boring to the required diameter in a reverse motion. It is recommended, to implement this, to combine the projection of the hole's boring axis with the axial forces transmission plane's of boring machine feeding mechanism [13][14][15]. After a pilot industrial operation of complexes for trenchless laying of communications, presented by a number of developers, including KuzSTU, it was found that the supply of the machine unit into and out from the mine face at horizontal boring process can be successfully carried out cyclically, if the following problems will overcome [16][17][18]:…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is taken into account that in order to increase the stability of boring equipment when boring horizontal holes of large diameter, it is possible to use a two-stage technology, which implies boring a small-diameter pioneer hole in a direct motion with its subsequent boring to the required diameter in a reverse motion. It is recommended, to implement this, to combine the projection of the hole's boring axis with the axial forces transmission plane's of boring machine feeding mechanism [13][14][15]. After a pilot industrial operation of complexes for trenchless laying of communications, presented by a number of developers, including KuzSTU, it was found that the supply of the machine unit into and out from the mine face at horizontal boring process can be successfully carried out cyclically, if the following problems will overcome [16][17][18]:…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the modern period puts a number of actual tasks for developers of auger complexes, including: -an expanding the the range of physical and mechanical characteristics of the rocks and soils under development and the diameter of the conducted holes for various purposes at the same time with reducing the energy intensity of the processes [5][6][7][8][9][10]; -an effective combination of tools with various methods of destruction of the face and devices for equipment's feeding to the face using various physical principles [11][12][13]; -the creation of an aggregate-modular gamma of sinking equipment with a new technical level, formed according to an open principle, with the possibility of flexible refinement of the configuration of complexes for specific boring conditions with the verification of each applied technical solution by computer modeling, which affects the economic component of each project [14][15][16]; -a complex increase in the automation level of boring operations, operations to remove of developed boring products to the edge of the pit, operations for mounting and dismaunting of sections of the auger bore string and casing strings during direct and reverse boring, and, as a result, the development of geotechnical robotic systems that allow unmanned horizontal auger sinking of horizontal and slightly deviated holes.…”
Section: Introductionmentioning
confidence: 99%